Mapping the position of the tourism villages in purworejo regency based on local potential unique - Sri Nugroho, Arif Julianto; Haris, Abdul; Tasari, Tasari; Setyawanti, Dandang; Jati, Agung Nugroho; Santoso, Gunawan Budi (Journal of Business on Hospitality and Tourism, 2022)
This study aims to determine the position of excellence of each tourism village so that it can determine the right marketing strategy to satisfy and improve the tourist experience. The study was conducted using a quantitative test approach (positivism) through multivariate multidimensional scaling statistical tests with SPSS package. The population in this study were domestic tourists and the public who visited the six tourism villages of Purworejo Regency. Sampling used purposive sampling as many as 112 respondents. The attributes in the questionnaire adapted from Vassiliadis include attractiveness, accessibility, facilities, community empowerment, marketing-promotion and institutional resources. The final stage of the research has formed a map of each tourism village so as to create village competitiveness in facing the era of creative economic growth through sustainable tourism after the Covid-19 pandemic in Purworejo Regency